Arte y ciencia en dos obras de María Fernanda Cardoso (2020)
Maria Fernanda Cardoso is a Colombian artist that has been incorporating scientific research as a central element in her artworks for over twenty years. Some of her main interests include the hidden world of minuscule species, the presence of art in the animal world, and the morphological reproductive characteristics of different species. Cardoso forms part of a group of scientists and artists from different backgrounds who have seen the potential of interdisciplinary collaboration and the value of creativity and sensitivity in the search for knowledge. This new perspective questions the limits of both fields in terms of method, scope, purpose, institution, and bias. The purpose of this text is to give an introductory look at two of Cardoso's most significant works under an interdisciplinary approach in order to establish their relationship with cultural institutions and scientific practice.